Status of phthalate esters pollution in facility agriculture across China: Spatial distribution, risk assessment, and remediation measures - Bai, Xiaoyun; Pan, Kaiwen; Shoaib, Noman; Sun, Xiaoming; Wu, Xiaogang; Zhang, Lin (The Science of the total environment, 2024)
The pervasive utilization of phthalate esters (PAEs) in plastic products has led to an emergent concern regarding the PAEs contamination in environmental matrices. However, the overall understanding of PAEs pollution in facility agriculture and its relevant risks remain limited. In this paper, the characteristics, health risks, and remediation measures of PAEs pollution in facility agriculture across China were analyzed. In general, PAEs pollution in facility agriculture soil in SWC and vegetables in SC were more serious than that in the other six regions (p < 0.05). The total level of six PAEs ranged from 0.053 to 5.663 mg·kg−1 in soil samples, nd (not detectable) to 12.540 mg·kg−1 in vegetable samples, with mean values of 0.951 mg·kg−1 and 2.458 mg·kg−1, respectively. DEHP and DnBP were dominant in both soil and vegetable samples with a total contribution of over 70 % of the six PAEs, but their concentrations were a little lower in soil samples. The PAEs concentrations of leafy, root, and fruit vegetables exhibited a descending trend. Correlation analysis revealed that the relationships between soil and vegetable PAEs concentrations remained inconclusive, lacking clear correlations. Furthermore, risk assessments indicated that the hazard quotient (HQ) for both total and individual PAEs in the vast majority of vegetable samples remained within acceptable thresholds. Meanwhile, all values for carcinogenic risks (CR) were confined within the range of 10−4. In conclusion, the study outlines remediation measures aimed at precluding and mitigating the environmental risks associated with PAEs exposure. These findings furnish a scientific foundation for the targeted assessment and judicious management of PAEs pollution within facility agriculture landscape of China. [Display omitted] •PAEs pollution in facility agriculture soil in SWC and vegetables in SC differed from the other six regions.•There were no clear correlations between soil and vegetable PEAs concentrations.•PAEs had a potential carcinogenic risk to human health via dietary route.•The individual or combined remediation measures might be suitable for heavily polluted regions.